The generation and transfer of agricultural knowledge: a bibliometric study of a research network - Thorpe, Peter; Pardey, Philip G. (SAGE Publications, 1990)
Publication-based indicators of agricultural research activ ity were developed to assist in the evaluation of the knowledge transfer component of an agricultural research network involv ing the six Southern Cone countries of South America (Argentina, Bolivia, Brazil, Chile, Paraguay and Uruguay). The generation of agricultural knowledge in these countries, as reflected by the CAB Abstracts database, has grown by about 50% over the period 1973 to 1982. The academic sector accounts for a substantial amount of this activity, about 40%. There is however significant cross-country variation in these figures.The transfer of agricultural knowledge among agncultural researchers in the region, and between these researchers and the world's research community, was studied using the SCI SEARCH database. The region generally relies heavily on international sources of knowledge; domestic sources are also important, especially in the larger systems, while regional sources are of only minor importance. There is some evidence, however, that in recent years regional sources may have be come relatively more important for the smaller research sys tems. There is also a suggestion that the region's researchers, particularly those in the smaller systems, are drawing on an ageing knowledge base.